Long-Term Outcomes and Safety Trends of Autologous Stem-Cell Transplantation in Non-Hodgkin Lymphoma: A Report From A Tertiary Care Center in India. (13th May 2022) - Kumar, Sudhir; Sharma, Atul; Pramanik, Raja; Pathak, Neha; Gogia, Ajay; Kumar, Akash; Kayal, Smita; Sharma, Vinod; Sahoo, Ranjit Kumar; Thulkar, Sanjay; Sharma, M.C.; Gupta, Ritu; et al.
Abstract : PURPOSE: Published experience with autologous stem-cell transplantation (ASCT) in non-Hodgkin lymphoma (NHL) from the Indian subcontinent is extremely limited. Here, we describe the activity and outcomes of this treatment modality at a large tertiary care center in India. PATIENTS AND METHODS: We retrospectively analyzed adult patients with NHL who were eligible for ASCT and autografted between January 1, 2002, and December 15, 2020, at our transplant unit. Toxicities, complications, and long-term outcomes were compared between patients who underwent transplant during 2002-2012 (group A) and 2013-2020 (group B). RESULTS: Overall, 80 patients (group A, n = 37; group B, n = 43) underwent ASCT using peripheral blood stem cells. At a median follow-up of 57.6 months, the 5-year event-free survival (EFS) and overall survival (OS) were 43.5% and 47.6%, respectively, for all patients. More recently (group B), patients had reduced 100-day transplant-related mortality (2.3% v 21.6%, P < .01), improved 3-year EFS (52.9% v 37.3%, P = .04), and superior OS (at 3-year; 63.4% v 43.2%, P = .02). Patients in group B also tolerated the procedure better, with improved resource utilization. In multivariate analysis, an International Prognostic Index (IPI) ≥ 3 at diagnosis adversely affected EFS (hazard ratio [HR] = 2.82, P = .009) and OS (HR = 2.84, P = .01) after ASCT. Low pretransplant serum albumin levels were associated with inferior EFS (HR = 2.68, P = .02) and transplant-related mortality (odds ratio = 10.80, P = .02) after ASCT. CONCLUSION: It is feasible to achieve comparable short- and long-term outcomes in patients with NHL undergoing ASCT in a resource-poor country with improved supportive care and expertise of the transplant team and center.